Optimal Placement, Sizing and Operating Power Factor of PV for Loss Minimization and Voltage Improvement in Distribution Network via DigSilent - Rasheed M.A.; Verayiah R.; Saleh B.-S. (Institute of Electrical and Electronics Engineers Inc., 2023)
Electric power factor; Fossil fuels; Global warming; Location; Silicon compounds; Conventional generation; Different voltages; IEEE 14 bus system; Loss minimization; Operating power; Optimal locations; Optimal placements; Voltage profile; System stability